2021
DOI: 10.3389/fnins.2020.614141
|View full text |Cite
|
Sign up to set email alerts
|

Beating Rate Variability of Isolated Mammal Sinoatrial Node Tissue: Insight Into Its Contribution to Heart Rate Variability

Abstract: BackgroundBecause of the complexity of the interaction between the internal pacemaker mechanisms, cell interconnected signals, and interaction with other body systems, study of the role of individual systems must be performed under in vivo and in situ conditions. The in situ approach is valuable when exploring the mechanisms that govern the beating rate and rhythm of the sinoatrial node (SAN), the heart’s primary pacemaker. SAN beating rate changes on a beat-to-beat basis. However, to date, there are no standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Thus, for mice, extrinsic mechanisms shift the power from LF to VLF under ABK conditions. In isolated SAN from rabbit ( Shemla et al, 2021 ) (as shown in Figure 2F ) or isolated heart ( Frey et al, 1996 ), the majority of PSD was in the VLF regime. Thus, for rabbits, the extrinsic contribution is minor compared to intrinsic pacemaker mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for mice, extrinsic mechanisms shift the power from LF to VLF under ABK conditions. In isolated SAN from rabbit ( Shemla et al, 2021 ) (as shown in Figure 2F ) or isolated heart ( Frey et al, 1996 ), the majority of PSD was in the VLF regime. Thus, for rabbits, the extrinsic contribution is minor compared to intrinsic pacemaker mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, to estimate the relative contribution of the extrinsic vs. intrinsic pacemaker mechanisms to the heartbeat interval of each mammal, we compared the ABK data to published results on isolated tissue ( Shemla et al, 2021 ) or isolated heart ( Frey et al, 1996 ). As shown in Figure 2E , in the isolated sinoatrial node (SAN) from mice (including only the intrinsic pacemaker mechanisms), the majority of PSD was in the LF regime, and the remaining power was in the VLF ( Shemla et al, 2021 ). Thus, for mice, extrinsic mechanisms shift the power from LF to VLF under ABK conditions.…”
Section: Resultsmentioning
confidence: 99%
“…From the point of view of mechanics, according to studies (Shemla et al, 2021;Weiser-Bitoun et al, 2021), the heart can be considered as a mechanism consisting of two discharge pumps formed into a closed system of tubes through which fluid (blood) circulates. In this case, the pumps create a directed blood flow in the appropriate direction.…”
Section: Resultsmentioning
confidence: 99%
“…З погляду механіки, згідно досліджень (Shemla et al, 2021;Weiser-Bitoun et al, 2021), серце можна розглядати як механізм, що складається з двох нагнітальних насосів, сформованих у замкнуту систему трубок, якими циркулює рідина (кров). У цьому випадку насоси служать для створення спрямованого потоку крові у відповідному напрямку.…”
Section: результати та їх обговоренняunclassified